Chiral Phosphoric Acid Promoted Chiral 1H NMR Analysis of Atropisomeric Quinolines - Wan, Junlin; Jiang, Jun; Li, Juan (Frontiers in Chemistry, 2021)
An efficient enantioselective NMR analysis of atropisomeric quinolines in the promotion of chiral phosphoric acid was described, in which a variety of racemic 4-aryl quinolines were well recognized with up to 0.17 ppm ΔΔδ value. Additionally, the optical purities of different nonracemic substrates can be fast evaluated via NMR analysis with high accuracy.